PENERAPAN MODEL PEMBELAJARAN KOOPERATIF CARD SORT UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS V SDN 003 PAGARAN TAPAH DARUSSALAM - Rusmayanti, Rusmayanti (Aksara Public, 2017)
This research is motivated by the lack of Learning Outcomes Civics class student V SDN 003 Pagaran Tapah Darussalam. Goals to be achieved in this research is to improve the students' learning outcomes Civics 003 class V SDN Pagaran Tapah Darussalam through cooperative learning model Card Sort undertaken during 1 month. This research was conducted in SDN 003 Pagaran Tapah Darussalam. Classes that thorough research is a Class V with the number of students as many as 20 people. Reaseact average student in initial tests categorized as low to the average value of 54.5, with the value of the percentage of completeness 25% or there are five students who otherwise completed and the remaining 15 students expressed not finished with a percentage of 75%, the first cycle, the value of average ability students rose to 64.5 in the medium category, with a percentage of completeness 60% or with a total of 12 students, the second cycle of average ability students have been categorized as good with an average value of 77.5, but with completeness 95%, where the value of the students have tercapikeempat completeness of (20%). Thus, this study was successful.